Risiko Kecurangan (Fraud) pada Pemerintah Daerah di Indonesia: Analisis Terhadap Temuan Audit - Amri, Abrar; Putri, Cut Widy Aulia (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2024)
The risk of fraud in local governments in districts and cities resulting from internal control deficiencies was reported in a series of audits carried out by the Audit Board. This research analyzes 23 Audit Reports on the Financial Report of Regency and City Regional Governments in Aceh for the 2022 Fiscal Year issued by the Aceh Province Representative of Audit Board. The Audit Result Reports on the Financial Reports of the Regional Government of Regency Municipalities in Aceh for the 2022 Fiscal Year observed in this research each contained between 10 and 21 findings with an average of 16 findings related to weaknesses in the internal control system and non-compliance with legislative regulations. Some of these entities, city districts, are indeed small. The 23 district and city government control audits, 18 (78%) which is considered to have a good internal control system and operates effectively, resulting in an audit opinion of "Unqualified ". The remaining 5 district and city government control audits (22%) identified internal control deficiencies and contains recommendations for improvement with a number ranging from 10 to 21 with an average of 16 recommendations per audit. Not all recommendations involve a lack of control, but most do (due in part to budgeting issues).